Assessment of sow herd frequency of PCV-2 using placental umbilical cord serum and serology in 18 breeding farms in Brazil - Lippke, Ricardo T.; De Conti, Elisa R.; Hernig, Luciana F.; Teixeira, Angélica P.; de Quadros, Fernando A.; Fiúza, Aparecida T.; Pereira, Juliana B.; Ulguim, Rafael da Rosa; Barcellos, David E. S. N.; Takeuti, Karine Ludwig (Frontiers in Veterinary Science, 2024)
Porcine circovirus type 2 (PCV-2) is the agent of one of the most important diseases in the swine industry. Although it has been controlled through vaccination, viremic piglets at birth may represent a risk by reducing vaccination efficacy. Since there are few reports on the viremic status of pre-suckling piglets regarding PCV-2 infection, we assessed the PCV-2 frequency in sows housed in 18 breeding farms with no history of clinical PCVAD in Brazil, using placental umbilical cord serum (PUCS). The selection criteria were: breeding farms with more than 1,000 sows; sows not vaccinated for PCV-2 at least for 2 years prior to the study; farms with no history of PCV-2 clinical disease in the last 12 months; and production systems with maximum of two sites. Blood from the umbilical cords in sow placenta or directly from piglet’s immediately after birth was collected from 30 litters on each farm for PCR. In addition, blood from 538 sows was collected for PCV-2 antibody detection. A total of 17.29% of the PUCS tested positive. The PCV-2 DNA was detected in PUCS from 94.4% of all farms. A total of 94.8% of the sow’s was positive for PCV-2 antibodies. However, seronegative sows were detected in 44.4% of farms. All 18 farms had at least 46.9% seropositive dams. A higher percentage of seronegative sows was observed for farms with more than 10% of PCV2-positive litters compared to those with ≤ 10% of PCV-2 positive litters (8.9 +/-1.7% vs 1.5 +/- 0.7%, P < 0.01, respectively).